NATURAL DISASTERS REVIEWED FROM THE PERSPECTIVE OF TAUHID RUBUBIYAH IBN TAYMIYAH - Wita Azani; Aprilinda M Harahap (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
The phenomenon of natural disasters is not only understood as a physical event, but in the theological perspective of Islam, especially Tawheed Rububiyah according to Ibn Taymiyah, disasters are a manifestation of the will and power of Allah SWT as the only Creator, Regulator, and Maintainer of the universe. This research aims to examine the meaning of natural disasters through the approach of monotheism rububiyah which is understood as part of reprimands, punishments, tests, and means of cleansing sins, all of which are reflections of the Divine will. The methodology of this research uses a qualitative-descriptive approach through literature study, by analyzing various Islamic literature, interpretation of the Qur'an, and Ibn Taymiyah's thoughts that are relevant to the theme of disaster and divinity. The results of the study show that natural disasters can be interpreted as a tool of spiritual and moral introspection for humanity, as well as a consequence of environmental damage due to human behavior that is not in accordance with the values of monotheism. In Ibn Taymiyah's view, the recognition of the rububiyah of Allah is not only a theoretical belief, but must be manifested in the form of an ethical and ecological responsibility to maintain the balance of nature. The conclusion of this study confirms that the understanding of monotheism provides a strong spiritual and ethical foundation in responding to natural disasters more wisely, making it a means to improve oneself, strengthen faith, and affirm the role of humans as the caliph of Allah on earth